2021
DOI: 10.3390/app11177813
|View full text |Cite
|
Sign up to set email alerts
|

Polyphenoloxidase (PPO): Effect, Current Determination and Inhibition Treatments in Fresh-Cut Produce

Abstract: Fresh-cut produce are quite popular among consumers due to their eating ease, high quality and functional content. However, some of the processing steps taking place during minimal processing (such as cutting, peeling, draining, etc.) might speed up decay, e.g., microbial growth, dehydration or browning. When it comes to the latter, polyphenol oxidase (PPO) plays an important role, being the center of many works focused on the understanding of its reaction mechanism and the application of conservative techniqu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 130 publications
0
14
0
Order By: Relevance
“…Polysaccharide‐based coatings have been studied by prior research to be effective in fresh‐cut preservation; not only exhibiting desirable mechanical properties, and film‐forming ability, but also having selective gas permeability (Pilon et al., 2015). Polysaccharide‐based coatings also showed antimicrobial action (Pilon et al., 2015) that might be beneficial to inhibit enzymatic browning, noting that microbial growth could increase enzymatic browning activity by worsening the cell integrity of apple tissue, provoking cell lysis, and leading to contact between browning enzymes and substrates (Nogales‐Delgado, 2021).…”
Section: Inhibition Of Enzymatic Browningmentioning
confidence: 99%
See 2 more Smart Citations
“…Polysaccharide‐based coatings have been studied by prior research to be effective in fresh‐cut preservation; not only exhibiting desirable mechanical properties, and film‐forming ability, but also having selective gas permeability (Pilon et al., 2015). Polysaccharide‐based coatings also showed antimicrobial action (Pilon et al., 2015) that might be beneficial to inhibit enzymatic browning, noting that microbial growth could increase enzymatic browning activity by worsening the cell integrity of apple tissue, provoking cell lysis, and leading to contact between browning enzymes and substrates (Nogales‐Delgado, 2021).…”
Section: Inhibition Of Enzymatic Browningmentioning
confidence: 99%
“…While for Red Rome, although it exhibited the highest chlorogenic acid content and high quantified phenolic concentration, it browned minimally (low Δ E and Δ C , moderate PPO and POD activity), which might be due to its less maturity than others (Serra et al., 2021). Maturity, selection of cultivars, and preharvest condition (climate, irrigation, rain conditions) may affect the quality and PPO activity of fresh‐cut fruits and vegetables (Nogales‐Delgado, 2021). However, a study found that the maturity did not significantly affect the PPO activity of Elstar, Fuji, and Mellow pulps, but PPO activity decreased significantly along with the maturity (ripeness) of Aori27 pulp, supported by decreased Δ E (after 24 h of storage) and TPC, compared to the immature and half‐mature Aori27 pulp (Holderbaum et al., 2010).…”
Section: Inhibition Of Enzymatic Browningmentioning
confidence: 99%
See 1 more Smart Citation
“…Decompartmentalisation and bruising of tissue lead to oxidative reactions such as enzymatic browning reaction and consequent generation of dark pigments (González-Aguilar, Ruiz-Cruz, Cruz-Valenzuela, Rodríguez-Félix, & Wang, 2004). Several authors have also reported the beneficial effect of essential oils delaying browning (Çandır, 2017;Nogales-Delgado, 2021;Zhou, Sun, Zou, Zhou, & Liu, 2021). Over time, chroma values of the samples tended to diminish indicating that the colour intensity of pineapple chunks decreased with storage, this tendency being significantly less accused in fruit that was stored in responsive packages.…”
Section: Controlmentioning
confidence: 99%
“…promotes the enzymatic reaction, with subsequent economic losses to the producers or manufacturers. The much appreciated fresh-cut minimally processed fruit and vegetable products are a class of foods also very susceptible to PPO browning [6]. PPO is an endogenous enzyme, which is naturally present in plant tissues, and it has also been referred to as polyphenol oxidase, catechol oxidase, tyrosinase, phenolase, catecholase, and o-diphenol oxidase.…”
Section: Introduction 1enzymatic Browning By Polyphenoloxidase (Ppo)mentioning
confidence: 99%